A new model for supplier selection by an integrated method FAHP-IFTOPSIS. (1st January 2012) - Ahmadi, Mostafa; Kantardjian, Sarkis L.
In a competitive environment, the selection of suppliers are the most critical issues facing manufacturing firms because the costs of raw materials and components may, in fact, comprise the major portion of a product's final cost. Selecting an appropriate supplier can significantly reduce purchasing costs, decrease production lead time, increase customer satisfaction, and strengthen corporate competitiveness. In this paper an integrated supplier selection model is presented in which fuzzy analytical hierarchy process (FAHP) method is used to determination of criteria weight and by using intuitionistic fuzzy technique for order performance by similarity to ideal solution (IF-TOPSIS) method suppliers are ranked in a multiple criteria decision making frame work.